plsdontcrashagainretard

Download as pdf or txt
Download as pdf or txt
You are on page 1of 6

1.

) :|4 − 2​x​| = 10 :4 − 2​x ​= ±10 :when taking + ve :4 −


2​x ​= 10 :−2​x ​= 6 :taking − ve :4 − 2​x ​= −10 :−2​x ​= −14
:x = log14

log2 ​:x = 3.81
2i)
: 1​
) ∗ (−4x) + ​−​1​
√1−4x ​:(1 − 4x)​−​1​2 ​:1 + (− 1​​ 2​ 4​
(−​1​ −1)
2​

∗ (−4x)​2 ​
2! ​ :1 + 2x + 6x​2
ii)
:(1 + 2x)(4 − 16x)​−​1​2 ​:(1 + 2x) ∗ 4​−​1​2​(1 − 4x)​−​1​2
(1 + 2x + 6x​2​
:​1​2​ ) + 2x(1 + 2x + 6x​2​)
(1 + 2x + 6x​2 ​
:​1​2​ + 2x + 4x​2 ​+ 12x​3​)
(1 + 4x + 10x​2 ​
:​1​2​ + 12x​3​) :coefficient
=5

3i) :p(x) = x​3 ​− 3ax +


4a :when x = 2 :p(x) =
0 :0 = (2)​3 ​− 3 ∗ 2a +
4a :0 = 8 − 2a :2a = 8
:a = 4

ii.
)

:x-2)x​2 ​-12x+16(x​2​+2x-8 [Use algebraic


division]

:(x − 2)(x​2 ​+ 4x − 2x − 8)
:(x − 2)(x + 4)(x − 2)

b
)
:p(x​2​) = x​6 ​− 12x​2 ​+ 16 :hence :x​2 ​= 2 and x​2 ​= −4 :x =
√2
Type euation here.

4) to be updated
5i)
:y = 8sinx

− ​tanx
2​

dy​ =
2 ​:​ dx ​
8dsinx

2​dx2 dxdtanx


dx 2​ −

2​dx2 dx​
​ ∗ ​dx ​2:=
​ :when 4cosx

dy​ − = ​sec​0 ​
2​ dx ​ 4
2​
x

:0 = 4cosx

− ​sec​
2​ 4
2​
x

:​sec​4 2​​ x
= ​4cosx
secsecx​ 1 ​ 3​
2 ​::: ​ cosx ​2 ​ 2​ x

==2

=2
2​

= ​cosx​
:​1​2 ​ 2 ​:x = 2​​ 3
6i.)
:3x​2 ​− 4xy + y​2 ​= 45 :​3dx​2
− 4(​dx​ ∗ y + ​dy​ ∗ x) + ​dy​2
dx ​ dx ​ dx ​

∗ ​dy​ = 0 ​
dy ​ dx ​ :6x − 4(y + xdy

) + ​2ydy
dx ​

=0​
dx ​ :6x − 4y − 4xdy

+ ​2ydy
dx ​

= 0 ​ dy​ (2y − 4x) = 4y − 6x ​


dx ​ :​ dx ​ :when x = 2 and y = −3
= ​4∗−3−6∗2 ​
:​dy​dx ​ 12​
2∗−3−4∗2 ​:​ 7

ii)not read
7)
=​
:​dy​dx ​ 6xe​x
y​
2​
:y​2​dy = 6xe​x​dx :∫y​2​dy = ∫6xe​x​dx
= 6x ∫e​x​
:​y​3​3 ​ dx − ∫((​dex
)e​x​ = 6xe​x ​ = 6xe​x ​
dx ​ dx)dx :​y​3​3 ​ − ∫6e​x​dx :​y​3​3 ​ − 6e​x ​+ c
= 6 ∗ 0 ∗ e​x ​
:when y = 2 and x = 0 :​(2)​3​3 ​ − 6e​0 ​+ c :c =
y​3​ = 6xe​x ​ =6∗
26​
3 ​:​ 3 ​ − 6e​x ​+ 26​
​ 3 ​:when x = 0.5 :​y​3​3 ​
0.5e​0.5 ​
− 6e​0.5 ​+ 26
​ 3​ ​:y = 3.34
8) to be updated.
9)
:2x​2 ​+ 5x + 2)4x​2 ​+ 5x + 3(2 :use algebraic
5x + 1
division.remainder = −5x − 1 :A = 2 :− ​
=B
(2x + 1)(x + 2) ​
+c
2x + 1 ​
x+2
:− 5x+1

= B + ​C(2x+1)
x+2 ​

(x+2) ​:when x = − 1​​ 2 ​:− 5∗−​


​ 1​2​+1
+2 =
​ B​
1​
−​ 2​ :B = 1 :− 5x+1

= ​B(x+2)
2x+1 ​

+C​
2x+1 ​ :when x = −2 :− 5x−2+1

=C​
2∗−2+1 ​ :C = −3 :2 + 1​
− ​3​
2x+1 ​ x+2 ​:∫ 2 + 1​
− ​3​ dx ​4​
2x+1 ​ x+2​ 0 ​:[2x + ln(2x+1)

− 3ln(x + 2)]​ 4​
2​ 0​ :[2 ∗ 4 + ln(2∗4+1)

− 3ln(4 + 2)] − [4 ∗ 0 + ​ln(2∗0+1)
2​

−​
2​ 3ln(0 + 2)] :[8 + ln(3) − 3ln(6) + 3ln(2)] :8 + ln(​3∗8
3​ )​
6​ :8 − ln(9)

You might also like

pFad - Phonifier reborn

Pfad - The Proxy pFad of © 2024 Garber Painting. All rights reserved.

Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.


Alternative Proxies:

Alternative Proxy

pFad Proxy

pFad v3 Proxy

pFad v4 Proxy